1994
DOI: 10.2337/diacare.17.8.901
|View full text |Cite
|
Sign up to set email alerts
|

Altered Postprandial Insulin Requirement in IDDM Patients With Gastroparesis

Abstract: OBJECTIVE To evaluate the effect of gastric emptying on postprandial insulinrequirement in insulin-dependent diabetes mellitus (IDDM) patients with and without gastroparesis. RESEARCH DESIGN AND METHODS Postprandial insulin requirement and gastric emptying were simultaneously evaluated in five IDDM patients with gastroparesis and in six control IDDM patients without gastroparesis. Postprandial insulin requirement after test-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 2 publications
(2 reference statements)
3
42
0
Order By: Relevance
“…[21][22][23][24][25][26] Although these GI symptoms are not considered to be important causes of mortality in T2DM, they have obvious negative influences on diabetes control, diabetes complications, and health-related quality of life. 23,27,28 In our study, both TAS30QW (nausea, 83.20%; vomiting, 88.52%) and LIX30BID (diarrhea, 84.76%) had higher risk for GI AEs when compared with placebo. Our results were similar to previous studies, which reported that GLP-1 RAs have a significant effect on GI AEs compared with other treatments for patients with T2DM.…”
Section: Discussionmentioning
confidence: 82%
“…[21][22][23][24][25][26] Although these GI symptoms are not considered to be important causes of mortality in T2DM, they have obvious negative influences on diabetes control, diabetes complications, and health-related quality of life. 23,27,28 In our study, both TAS30QW (nausea, 83.20%; vomiting, 88.52%) and LIX30BID (diarrhea, 84.76%) had higher risk for GI AEs when compared with placebo. Our results were similar to previous studies, which reported that GLP-1 RAs have a significant effect on GI AEs compared with other treatments for patients with T2DM.…”
Section: Discussionmentioning
confidence: 82%
“…10 However, previous investigators have advocated the combined use of scintigraphy for the solid phase and the paracetamol method for the liquid phase. [17][18][19] The combination technique enables the use of a radiolabeled liquid to be omitted, with a reduction in the amount of the patient's radiation exposure, and simplification of the test procedures. 7 Furthermore, use of saliva in place of plasma makes the isotopeparacetamol technique more convenient.…”
Section: Discussionmentioning
confidence: 99%
“…with gastroparesis, less insulin is required to maintain euglycemia than in those with normal gastric emptying (91).…”
Section: Figure 5-relationship Between Glycemic Response (Area Under mentioning
confidence: 99%